Effects of Pyrroloquinoline Quinone (PQQ) and Coenzyme Q10 on Mitochondrial Genes, MitomiRs and Cellular Properties in HepG2 Cell Line: Effects of PQQ and CoQ10 on Cellular Properties - Nalbant, Muhammed Ali; Eroğlu, Onur (Cellular and Molecular Biology, 2023)
Our study aimed to reveal the effects and changes, antioxidant metabolism (Oxidative Stress), inflammatory response, mitochondrial biogenesis and mitochondrial dysfunction characteristics in hepatocellular carcinoma cell line HepG2; that occur in genes (NRF-1, NRF-2, NFκB and PGC-1α) and miRNAs (miR15-a, miR16-1, miR181-c) that can control related features. To investigate the effects of Pyrroloquinoline quinone (PQQ) and Coenzyme Q10 (CoQ10) in HepG2, and their effects on cell viability, lateral cell migration, gene expression and miRNA expression levels were investigated. If the data we have obtained are evaluated in terms of anti-cancer effectiveness, the most effective use of CoQ10 can be defined as the use alone rather than the combined use. According to the results of the wound healing experiment, we determined that Pyrroloquinoline quinone and combined drug application increased the wound closure area and cell proliferation compared to the control group, while CoQ10 application decreased it. We found that Pyrroloquinoline quinone and Coenzyme Q10 exposure in the HepG2 cell line increased Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) expression but not NRF-1 gene expression. We reported only a small increase in expression of the NRF-2 gene in the Pyrroloquinoline quinone application compared to the control group. We found that only Pyrroloquinoline quinone and CoQ10 application caused more expression increase in the Nuclear Factor kappa B (NFκB) gene compared to combined application. Pyrroloquinoline quinone and CoQ10 administration down-regulated the expression levels of miR16-1, miR15a and miR181c. The use of Pyrroloquinoline quinone and CoQ10 is effective on epigenetic factors, miR-15a, miR-16-1 and miR181c are important candidate biomarkers in hepatocellular carcinoma and diseases accompanied by mitochondrial dysfunction.